The bone marrow niche components are adversely affected in sepsis - Fan Yin; Han Qian; Caiwen Duan; Botao Ning (Molecular Biomedicine, 2020)
Abstract Multiple organ dysfunction is an important cause of death in patients with sepsis. Currently, few studies have focused on the impact of sepsis on bone marrow (BM), especially on the cell components of BM niche. In this study, we performed mouse sepsis models by intraperitoneal injection of LPS and cecal ligation and puncture (CLP). The changes of niche major components in the mouse BM among vascular structures, mesenchymal stem cells and Treg cells were observed and analyzed. The results showed that pathological changes in BM was earlier and more prominent than in other organs, and various cell components of the BM niche changed significantly, of which vascular endothelial cells increased transiently with vascular remodeling and the regulatory T cells decreased over a long period of time. These results indicated that the components of the BM niche underwent series of adaptive changes in sepsis.